2011
DOI: 10.1007/s11249-011-9828-0
|View full text |Cite
|
Sign up to set email alerts
|

Friction of the Human Finger Pad: Influence of Moisture, Occlusion and Velocity

Abstract: The current paper describes an experimental study of the friction of the human finger pad. The data highlight the role of sweat secretion and contact occlusion in producing wide-ranging values for the coefficient of friction that are particularly sensitive to the tribological configuration, sliding velocity, surface roughness and porosity of the counterbody. In particular, the large coefficients of friction typically observed on dry smooth surfaces are associated with a relatively damp interface, and can be co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
149
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(164 citation statements)
references
References 81 publications
(152 reference statements)
11
149
0
1
Order By: Relevance
“…Thus, we can tentatively suggest that the contact formation kinetics divide the tactile world into broad categories of materials: smooth and impermeable surfaces that could be subdivided into those that are hard (glass, glazings, polished metals) or those that are softer than keratin (rubbers, certain polymers); rough surfaces that can also be divided into those that are made of relatively hard and soft materials; and porous surfaces (paper, wood, fabrics) that further modify the kinetics of contact formation together with hydrophobicity. For example, it has been observed that, for filter paper, the friction and hence, Atrue decrease with the contact time, since the secreted sweat is absorbed, leading to reduction in the compliance of the keratin (2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we can tentatively suggest that the contact formation kinetics divide the tactile world into broad categories of materials: smooth and impermeable surfaces that could be subdivided into those that are hard (glass, glazings, polished metals) or those that are softer than keratin (rubbers, certain polymers); rough surfaces that can also be divided into those that are made of relatively hard and soft materials; and porous surfaces (paper, wood, fabrics) that further modify the kinetics of contact formation together with hydrophobicity. For example, it has been observed that, for filter paper, the friction and hence, Atrue decrease with the contact time, since the secreted sweat is absorbed, leading to reduction in the compliance of the keratin (2).…”
Section: Discussionmentioning
confidence: 99%
“…During a period of many seconds, several phenomena take place at different length scales and timescales that eventually lead to a stable contact state, where the flattened apices of the ridges establish a uniform contact with the counter surface. Here, we observed that the so-called "true contact area," which quantifies the amount of material in intimate contact (i.e., in atomic proximity) (1,2), varies dynamically over a period of many seconds, while the apparent, or gross, contact area, by and large, remains unchanged through time.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The contact mechanics is influenced by the material and microgeometry of both the surfaces in contact, skin hydration, normal load and the relative velocity of the surfaces in contact. Finger pad friction properties were measured against a wide range of materials so far such as packaging materials [3], textiles [4,5],metals [6][7][8], polymers [6,8] and glass [9,10] to name a few. The effect of the interacting surface's microgeometry on finger friction has been explored in studies on ridged surfaces with different ridge geometries to understand their effect on finger friction [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of applied variables like normal force, sliding velocity and lubricants on finger pad friction has also been well characterized [6,8,14]. Inherent skin related phenomena like occlusion, sweating and the sensitivity of coefficient of friction to these conditions were well investigated [9,10]. More recently, Derler et al identified ploughing and abrasion as important friction mechanisms during repetitive rubbing of fingerpad on abrasive surfaces [15].…”
Section: Introductionmentioning
confidence: 99%